2005
DOI: 10.1002/pssc.200460189
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance study of Cr 3+ and Fe 3+ centers in hexagonal Cs 2 NaAlF 6 and Cs 2 NaGaF 6 crystals

Abstract: Na nuclei. The correlation between spin Hamiltonian parameters and crystallographic data is discussed. The results support the earlier identification of the Cr 3+ centers in these crystals from optical measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
3
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
3
3
0
Order By: Relevance
“…The D parameter values for both sites were D = −0.2540(5) cm −1 (for the S1 site) and −0.3560(5) cm −1 (for the S2 site). By comparing our values to those reported in the literature, a reasonable agreement is found for the magnitude of this parameter [19,[23][24][25]37]. Finally, using the transitions intensities, we obtained that 61% of Cr 3+ ions occupy the S2 site and 39% occupy the S1 site, which are close to the amount of Al 3+ in each site.…”
supporting
confidence: 86%
See 2 more Smart Citations
“…The D parameter values for both sites were D = −0.2540(5) cm −1 (for the S1 site) and −0.3560(5) cm −1 (for the S2 site). By comparing our values to those reported in the literature, a reasonable agreement is found for the magnitude of this parameter [19,[23][24][25]37]. Finally, using the transitions intensities, we obtained that 61% of Cr 3+ ions occupy the S2 site and 39% occupy the S1 site, which are close to the amount of Al 3+ in each site.…”
supporting
confidence: 86%
“…Other successful examples consist of perovskite-type oxides [11], metal-organic frameworks containing gadolinium [12], and molecular nanomagnets, such as Mn 32 [13] and Fe 14 [14]. However, very few studies have so far reported on caloric effects in fluoride systems [15][16][17], which is the aim of this paper.From the point of view of optical and structural properties, Cs 2 NaAl 1−x Cr x F 6 elpasolite single crystals, which crystallize in the R3m space group, have been thoroughly investigated [18][19][20][21][22][23][24][25][26][27]. The choice of the Cr 3+ ion as a doping impurity is justified by the fact that its 3d unfilled shell produces electronic transitions that increase the luminescent properties and the quantum yield of the material [20,[27][28][29].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicate that the degree of local distortion on the sites occupied by Cr 3+ ions is greater in Cs 2 NaAlF 6 :Cr 3+ compared to related compounds. Most recent electron paramagnetic resonance and electron-nuclear double resonance experiments support the spectroscopic results [13].…”
Section: Introductionsupporting
confidence: 54%
“…From the point of view of optical and structural properties, Cs 2 NaAl 1−x Cr x F 6 elpasolite single crystals, which crystallize in the R 3m space group, have been thoroughly investigated [15][16][17][18][19][20][21][22][23][24] . The choice of the Cr 3+ ion as a doping impurity is justified by the fact that its 3d unfilled shell produces electronic transitions that increase the luminescent properties and the quantum yield of the material 17,[24][25][26] .…”
mentioning
confidence: 99%